TRIM21-mediated PRMT1 degradation attenuates colorectal cancer malignant progression - Menghan Cao; Zhiying Shao; Xingyou Qian; Miaolei Chen; Chuyin Deng; Xintian Chen; Tingting Tang; Kaixu Zhang; Sufang Chu; Junnian Zheng; Jin Bai; Zhongwei Li (Cell Death and Disease)
Abstract Tripartite motif-containing 21 (TRIM21) plays a crucial role in antiviral responses and autoimmune diseases. While the impact of TRIM21 on cancer has been studied in various tumors, its role in colorectal cancer (CRC) remains unclear. In this study, we found that TRIM21 expression is reduced in primary CRC tissues. Low levels of TRIM21 in CRC are associated with unfavorable clinicopathological characteristics and shorter survival. Furthermore, we demonstrate that TRIM21 suppresses the proliferation, tumorigenesis, migration, and metastasis of CRC cells by promoting the ubiquitination-mediated degradation of PRMT1. These findings suggest that TRIM21 holds potential as a valuable predictive biomarker for assessing the prognosis of CRC patients.